Transformasi Tata Kelola Badan Usaha Milik Desa (BUMDes) pada Era Digital - Wulandari, Gusti Putu Mutia; Lestari, Ni Putu Nina Eka (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Villages, as the smallest administrative entities in Indonesia, play a significant role in the national development process. BUMDes is a business entity that is public, owned by the village, and uses funds from the village government for the benefit of the village community. The aim of this research is to determine the transformation process of BUMDes governance from the manual era to the digital era, to determine the role of Good Corporate Governance and digitalization in the BUMDes governance transformation process, to explore the internal and external factors that influence BUMDes in the governance transformation process, and to understand the transformation strategy for BUMDes governance in the digital era. This research uses qualitative methods carried out at BUMDes Kartika Lestari. The data analysis technique used is the interactive data analysis technique by Miles and Huberman. The research results show that the transformation of the governance of BUMDes Kartika Lestari was carried out from 2019, where there were many experiments until an application was obtained that was in line with the objectives in managing BUMDes. The implementation of GCG and digitalization in carrying out the transformation of BUMDes governance is carried out following the 5 principles of GCG, namely Transparency, Accountability, Responsibility, Fairness and Independence. Internal factors and external factors greatly influence BUMDes. The strategy implemented by BUMDes is adding programs, aligning technology, adding business units, improving human resources, collaborating with third parties.